Три ступені розвитку продуктивних сил первіснообщинної суперформації - Генінг, В.Ф. (Археологія, 1989)
Ця стаття продовжує дослідження формаційної структури первісності на предмет виділення у рамках суперформації докласового суспільства окремих соціальних формацій і вміщує аналіз технологічного способу виробництва первісності, реконструйованого за даними сучасної археології. Результати аналізу служать емпіричною основою виділення трьох якісно відмінних ступенів у розвитку виробничих сил первіснообщинного способу виробництва і тим самим трьох соціальних формацій: кровноспорідненої сім’ї, родової общини, племінного ладу. Продолжая исследование проблемы выделения в первобытности социальных формаций как прогрессивных стадий в развитии способа производства доклассовых обществ (см. «Археологія», № 2, 1989), в статье анализируется технологический способ производства, реконструируемый на основе современных достижений археологии. Это служит эмпирической базой при рассмотрении ступеней развития производительных сил со стороны их организационных форм. Анализ выполнен в аспекте развития пищевого и непищевого производства, технических достижений по освоению природных ресурсов (освоение энергии внешней среды) и общей структуры технологии деятельности. Proceeding with the investigation of the problem on distinguishing social formations in the primitive society as progressive stages in the development of the production mode of pre-class societies (see “Arkheologiya”, N2, 1989), the paper embraces analysis of the technological mode of production reconstructed on the basis of the latest achievements in archaeology. It serves as empirical foundation when considering stages in development of productive forces in terms of their organization forms. The analysis is performed in the aspect of food and non-food production development, engineering achievements in exploration of natural resources (exploration of the environmental power) and general structure of the activity technology. Three stages differing between themselves and considered in frames of social formations are distinguished:
The 1st stage (formation of consanguineous family) —formation of the technological system of productive activity in the elementary form of a binary act based on thè^ usage of the simplest manual stone and ivory tools with percussive and missile functions and simple cooperation of mascular forces of individuals from a particular community. Food demands are satisfied by appropriation of ready natural products procured by hunting and gathering. In production of labour facilities natural raw material — stone, ivory and wood are processed by means of the simplest mechanical techniques with percussive functions. This is the first stage in formation of social production, based on the collective forms of labour — simple cooperation in the community with sex-age labour division,
The 2nd stage (formation of the stem society) — technology of productive activity develops into a “technological chain” (as a sum of successively connected simple acts). A sphere of collective activity is expanded, new mechanical ways for performing labour operations being introduced. Producing forms in obtaining products of consumption are developed: agriculture and cattle breeding using biological power of nature in food production; creation of new materials (pottery, leather, fabric with application of mechanical treatment, chemical reactants and fire energy) — in craft. Inner-community technological division of labour (separation of skilled craftsmen) forms a complex structure of social production of the community with flourishing state of collective forms of labour. This process is crowned by the first large social division of labour — specialization in one type of procuring food production.
The 3d stage (formation of the tribal system) — introduction of flow charts — structure of complex activity, based on cooperation of “technological chains” when creating product of the same quality causes a decrease of productive collectives, their cooperation and exchange of products including half-finished products. Thé flow chart underlies complex farming of particular communities and their specialization in the rational usage of the local natural resources. Inner-community division of labour ever more turns into the social one — specialization of individuals and groups of community in production of different types of products and fulfilment of different social functions — power, mana-gement and ideology. A determining tendency of the given stage is the growth of parcel ar tendencies in collective forms of labour. These tendencies result is economical isolation of a family, first — a big one and then — a monogamie. All this is a step to the production technique of class society.